Documents and court opinions on Bhopal gas leak disaster case for course on tort-II (Industrial and Mass torts). - Menon, N.R. Madhava (Banglore, 1991)
Tort Law is usually taught in the undergraduate programme as a single course extending one academic term. The locus of the course has been on principles of liability, general defences in tort actions and a few conventional torts such as trespass, nuisance, negligence, defamation etc.
Keywords: Law- India